The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13662-018-1481-6
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations and chaos in a discrete SI epidemic model with fractional order

Abstract: In this study, a new discrete SI epidemic model is proposed and established from SI fractional-order epidemic model. The existence conditions, the stability of the equilibrium points and the occurrence of bifurcation are analyzed. By using the center manifold theorem and bifurcation theory, it is shown that the model undergoes flip and Neimark-Sacker bifurcation. The effects of step size and fractional-order parameters on the dynamics of the model are studied. The bifurcation analysis is also conducted and our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Let S 1 = s m mΓ(m) and S * be a perturbation in the bifurcation parameter S 1 , where |S * | << 1. Then a perturbation form of model (14) can be represented as [35] x n+1 = x n + (…”
Section: Hopf Bifurcation and Its Stabilitymentioning
confidence: 99%
“…Let S 1 = s m mΓ(m) and S * be a perturbation in the bifurcation parameter S 1 , where |S * | << 1. Then a perturbation form of model (14) can be represented as [35] x n+1 = x n + (…”
Section: Hopf Bifurcation and Its Stabilitymentioning
confidence: 99%
“…Fractional models can describe complex physics problems more clearly and concisely, especially the nonlinear model and their physical meaning. Research has shown that the fractional order equation o ers a possibility for the situation that the traditional integer order equation cannot model [3]. Most importantly, the most prominent feature of the body's immune system is about its memory.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling for various biological problems is considered to be an exciting research area in the discipline of applied mathematics. In the literature, many biological phenomena were modeled and formulated mathematically [1][2][3][4][5][6]. For example, Liu and Xiao established a predator-prey system in discrete time to analyze the local stability and the bifurcation of solutions around the positive equilibrium point [4].…”
Section: Introductionmentioning
confidence: 99%